Pemeliharaan Sistem Fotovoltaik di Sekolah Menengah Kejuruan Muhammadiyah 2 Turi. Sleman - Muhammad Nadjib; Fitroh Anugrah Kusuma Yudha (Universitas Muhammadiyah Yogyakarta, 2023)
SMK Muhammadiyah 2 Turi in Sleman Regency, Special Region of Yogyakarta, received photovoltaic system assistance from a government grant. Photovoltaic is a technology that converts solar energy into electrical energy. This equipment is used as a backup when the power is off. However, the partners did not understand how to maintain the photovoltaic system. The proposed solution was to conduct training on photovoltaic system maintenance. This activity aimed to provide knowledge for those in charge of operations on photovoltaic system maintenance methods. The applied method was tutorial/training and practice. The presented materials were photovoltaic technology, installation, and maintenance. The evaluation was to compare test results before and after training. The evaluation showed that this training increased participants' knowledge about photovoltaic systems by 25.29%. This training can be further developed in a community environment by adding photovoltaic installations in the vicinity. Communities should be able to carry out maintenance independently so that the performance of the photovoltaic system and the durability of its components are optimal.